EIB Working Papers 2019/07 - What firms don’t like about bank loans - Ségol, Matthieu; Kolev, Atanas; Maurin, Laurent (European Investment Bank, 2021)
We use the association between non-financial firms and their banks, an information available in the European Investment Bank Investment Survey (EIBIS), to disentangle the effects of borrowers’ and lenders’ financial weakness on the satisfaction with the loan contracted. The dataset matches survey data of non-financial firms about their satisfaction with bank lending with their financial data and the financial data of their banks. We find evidence of both demand and supply factors determining firm satisfaction with bank loan financing: non-financial firms with weaker finances and those financed by weaker banks are less satisfied with their bank financing. We also find that the impact of supply factors differs across regions within the EU: the effect of bank’s financial weakness on borrower satisfaction is not significant in core countries but is in periphery countries.